Transjugular Intrahepatic Portosystemic Shunt Reduction for Medically Refractory Hepatic Encephalopathy - Brandon Toliver; Matthew Thornburg; Adam Schmitz; Paul Haste (Journal of Clinical Interventional Radiology ISVIR)
Purpose Transjugular intrahepatic portosystemic shunt (TIPS) is an established intervention for symptomatic portal hypertension, with many patients experiencing hepatic encephalopathy (HE) as an undesirable side effect. For medically refractory HE, TIPS reduction can decrease the burden of neurotoxic metabolites. This study aimed to evaluate the efficacy of TIPS reduction for the treatment of medically refractory post-TIPS HE.